COVID‐19 in kidney transplant recipients; a DALMATIAN single‐center experience. Issue 1 (19th June 2022) - Dogas, Tina; Brkovic, Tonci; Novak, Ivana; Radic, Josipa
Abstract: Introduction: We aimed to explore COVID‐19 severity, complications, and outcome predictors in the Dalmatian population of kidney transplant recipients (KTRs). Methods: KTRs confirmed with acute COVID‐19 infection until May 2021 were included and followed up for 6 months. Results: Out of 50 KTRs average aged 63 years, 36 (72%) were men. Nine (18%) KTRs had no pulmonary infiltration, and twenty‐nine (58%) did not require oxygen supplementation. Bilateral pulmonary infiltrates had 29 (58%) while high‐flow nasal cannula or mechanical ventilation required 8 (16%) KTRs. The mortality rate was 16%. Acute kidney injury developed in 18 (36%), and acute renal replacement therapy required 2 (4%) KTRs. Nine (18%) KTRs were subsequently rehospitalized. Chronic COVID‐19 syndrome reported 23 (58%) KTRs. Conclusions: D‐dimers were found to be the key prognostic factor of clinical complications, emphasizing the importance of underlying thrombotic microangiopathy. Optimal immunosuppressant adjusting in KTRs with acute COVID‐19 infection remains to be clarified.